Hubungan Hukum dan Kekuasaan - Salman Luthan (Jurnal Hukum IUS QUIA IUSTUM, 2007)
Human being is a social creature which needs each other to fulfill the requirement of live, anywhere he or she lives. And every place of human live have rules to keep the peacefulness and justice among the individuals. These rules or laws were born to be adapted for value expanding in society community compiled by people who have power. Among law and power cannot be dissociated because law made by authority and the authority obtain the power passing the laws.